Implementing the ISO 9000 steps at the local level: A survey of Malaysian local authorities - Muhammad Rosmizan Abdul Wahab,; Shardy Abdullah,; Arman Abdul Razak, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
The implementation of the ISO 9000 quality management system within the Malaysian local government organizations has involved multiple steps and the consideration of multiple aspects. This study identifies and discusses the preferred steps used by Malaysian local authorities in implementing the ISO 9000. Quantitative data were obtained through a questionnaire survey of randomly sampled 53 local authorities. Results from the analysis show that most of the Malaysian local authorities were inclined to use the 11 implementation steps that have been proposed by the government as a guide to implement ISO 9000 within their respective organizations.